Service Learning in Premarital Guidance to Enhance the Religious and Psychological Readiness of Prospective Brides and Grooms - Sahputra, Dika; Sihombing, Firly Syahira; Sasmitha, Hesti; Panjaitan, Putri Rahmadani; Sari, Indah; Suhartika, Desmy; Azris, Dian Novelia; Sihombing, Hendra Pratama; Ritonga, Dandi Fhadillah (PT Agung Media Publisher, 2025)
Premarital guidance plays a vital role in preparing prospective brides and grooms for marriage by enhancing their religious and psychological readiness. Integrating Service Learning into this guidance program offers an experiential and participatory approach that may improve the effectiveness of preparation. This study employed a qualitative descriptive method with a Service Learning framework, involving five pairs of prospective couples and one religious counselor at the Religious Affairs Office in Percut Sei Tuan. Data were collected through participant observation and in-depth interviews, focusing on the implementation process and its impact on couples’ readiness. Findings indicate that Service Learning-based premarital guidance significantly improves couples’ understanding of Islamic marriage principles and strengthens their emotional maturity and coping skills. Interactive activities and reflections promoted deeper internalization of religious values and enhanced psychological preparedness for marital challenges. The participatory nature of Service Learning fosters moral commitment and emotional resilience essential for harmonious family life. Despite challenges such as limited time and participant variability, this approach effectively combines spiritual and psychological preparation, contributing to the development of stable and fulfilling marriages.